O trabalho de grupo na aula de língua materna: contributos para o desenvolvimento de competências verbais orais - Luzia da Conceição Bastos Alves Lage (Universidade do Minho, 2006)
Peer interaction in a group work context is a worthwhile alternative to the mosttraditional and common form of classroom interaction (teacher@whole class),as it contributes to the development of oral competences (object of our study).Data from the analysis of the corpus ten classes of group work, with 8thform students , based on two groups of categories modes of interactionand problems of interaction , show that students used language in a varietyof functions, which doesnt occur when they simply answer to the teachersquestions; on the other hand, a low frequency of problems of interaction.Beyond the interest of these data regarding a comparison withteacher@whole class interaction, the need of a particular focus on differentaspects of peer talk (turn-taking, variables of influence, among others) ishighlighted, in order to understand the pedagogical implications it demands